2012
DOI: 10.1128/iai.05544-11
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Interleukin-17 in an Experimental Legionella pneumophila Pneumonia Model

Abstract: Interleukin-17 (IL-17) is a key factor in T helper type 17 (Th17) lineage host responses and plays critical roles in immunological control of a variety of infectious diseases. Although Legionella pneumophila, an intracellular bacterium found widely in the environment, often causes a serious and life-threatening pneumonia in humans, the contribution of IL-17 to immune function during Legionella pneumonia is unknown. In the present study, we used an experimental Legionella pneumonia infection to clarify the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 55 publications
(50 reference statements)
4
35
1
1
Order By: Relevance
“…IL-17 is important for defence of the respiratory tract against bacterial pathogens including Staphylococcus aureus, Pseudomonas aeruginosa and Legionella pneumophila infections in mice [30][31][32]. In the present study, IL-17A receptor subunit A gene expression was identified in bTEC, consistent with prior findings in human airway epithelial cells [33].…”
Section: Discussionsupporting
confidence: 81%
“…IL-17 is important for defence of the respiratory tract against bacterial pathogens including Staphylococcus aureus, Pseudomonas aeruginosa and Legionella pneumophila infections in mice [30][31][32]. In the present study, IL-17A receptor subunit A gene expression was identified in bTEC, consistent with prior findings in human airway epithelial cells [33].…”
Section: Discussionsupporting
confidence: 81%
“…It is possible that sustained CXCL2 levels allow for continued recruitment of new neutrophils in an attempt to resolve the infection, although other chemokines or alternative neutrophil chemoattractants such as complement split products and/or bacterium-derived N-formyl-methionyl peptides (f-MetLeu-Phe) not examined in the current study may also participate in this process. IL-17 is an important antimicrobial cytokine, known to play an important role in the response to brain abscesses and cutaneous infections caused by S. aureus as well as other models of infection (1,12,24,30,33). In the setting of a catheter-based infection, IL-17 expression is significantly higher in infected than in sterile …”
Section: Fig 4 Catheter-associated Bacterial Growth Is Significantly mentioning
confidence: 99%
“…In a recent investigation, Il17a/Il17f −/− mice on a Balb/c background were utilized to show that IL-17A/F is important for controlling bacterial burden, inducing neutrophil influx into the lung, and for survival in response to L. pneumophila 15 . However, to further expand upon this initial study, we used: 1) single and double knockout mice on C57Bl/6 background and antibody blocking in A/J mice; 2) the role of IL-17A or IL-17F individually or together are important for host defense; 3) bone marrow chimeras and adoptive transfer experiments to determine which cell types are responsible for IL-17A and IL-17F production; 4) IL-17 homodimer (IL-17A or IL-17F) or heterodimer (IL-17A/F) to determine which is more effective at inducing host resistance; and 5) IL-17-mediates IFN-γ production via paracrine manner to induce host defense.…”
Section: Introductionmentioning
confidence: 99%